Pineal Region Tumor with Ventricular Extension with Hydrocephalus Removed by Supracerebellar Infratentorial Approach in a 19-Year-Old Female: A Case Report (Bangladesh Journal of Neurosurgery, 2024)
Pineal region tumors are uncommon, accounting for d”1% of intracranial tumors in adults and 3–8% of pediatric brain tumors. Getting an epidermoid in pinealregion is also very rare. In 1928 Cushing was the first to report the pineal localization of the epidermoid cyst.We report a case of pineal epidermoid with ventricular extension with obstructive hydrocephalus, which was diagnosed depending on magnetic resonance imaging (MRI) findings. Knowing its benign nature, at first we planned for an Endoscopic Third Ventriculostomy and later on a gross total removal was done.Bang. J Neurosurgery 2023; 13(1): 41-43